A privacy policy for myline - Mohamud Abdi, Isse (2014)
MyLinE is a self-access online resource for learning in English that is used by public university students in the country. The English resource is used by students to improve their English language communication skills and to compete National Online Quizzes and competitions held every semester. Such a system collects 0students? personally identified information to provide students a username and password to access the English resources. There should be a privacy policy which is posted on the system that clearly states students about how the personal data is collected, used and protected. This project focuses on developing a suitable privacy policy for MyLinE. An effective privacy policy consists of seven basic features and based on these seven, a requirement form is made to collect all the related information from the organization to develop a privacy statement. Based on the data collected, the researcher proposes a privacy policy for MyLinE. This privacy policy helps users to understand how MyLinE handles the personal information stored in the system database